Ovarian and uterine development and hormonal feedback mechanism in a 46 XX patient with CYP19A1 deficiency under low dose estrogen replacement. (May 2015) - Burckhardt, Marie-Anne; Obmann, Verena; Wolf, Rainer; Janner, Marco; Flück, Christa E.; Mullis, Primus E.
Abstract Background: Aromatase deficiency may result in a complete block of estrogen synthesis because of the failure to convert androgens to estrogens. In females, this results in virilisation at birth, ovarian cysts in prepuberty and lack of pubertal development but virilisation, thereafter. Objective and methods: We studied the impact of oral 17β-estradiol treatment on ovarian and uterine development, and on LH/FSH and inhibin B during the long-term follow-up of a girl harboring compound heterozygote point mutations in the CYP19A1 gene. Results: In early childhood, low doses of oral 17β-estradiol were needed. During prepuberty treatment with slowly increasing doses of E2 resulted in normal uterine and almost normal development of ovarian volume, as well as number and size of follicles. Regarding hormonal feedback mechanisms, inhibin B levels were in the upper normal range during childhood and puberty. Low doses of estradiol did not suffice to achieve physiological gonadotropin levels in late prepuberty and puberty. However, when estradiol doses were further increased in late puberty levels of both FSH and LH declined with estradiol levels within normal range. Conclusion: Complete aromatase deficiency provides an excellent model of how ovarian and uterine development in relation to E2, LH, FSH and inhibin B feedback progresses from infancy to adolescence.